Risk management and dynamic network performance: an illustration using a dual banking system - Kweh Q.L.; Lu W.-M.; Nourani M.; Ghazali Mohd Zain M.H. (Routledge, 2023)
This study applies dynamic network data envelopment analysis to compare a dual banking system, namely conventional and Islamic banks, with emphasis on risk measures. Non-oriented, variable return-to-scale dynamic network slacks-based measure is used to model the banking performance for the period 20082012. Under the consideration of risk measures, the findings highlight that Islamic banks excel in managerial efficiency while conventional banks surpass in profitability efficiency. Furthermore, the regression results find that the number of directors on the risk management committee has a positive impact on banking performance. Meanwhile, the high number of independent directors improves the profitability efficiency but worsens the managerial efficiency. 2018 Informa UK Limited, trading as Taylor & Francis Group.